Research progress on the synergies between heat waves and canopy urban heat island and their driving factors - Shi, Tao; Liu, Lei; Wen, XiangCheng; Qi, Ping (Frontiers in Environmental Science, 2024)
Under the background of global warming and accelerating urbanization, the interaction between heat waves (HWs) and canopy urban heat island (CUHI) has become one of the focuses in the field of global climate change research. This paper comprehensively reviewed and summarized the research process on the synergies of HWs and CUHI and their influencing mechanism. The coupling effect between HWs and CUHI remains debated, which may be related to the use of different standards to define heat wave events. The spatiotemporal differences in the synergies between HWs and CUHI was also influenced by climate background and local circulation. For instance, scholars have reached different conclusions regarding the stronger synergistic effect between daytime and nighttime in cities with different climate backgrounds. In addition, the modulation of urban morphological structure to the synergies between HWs and CUHI can not be ignored. In the future, it is necessary to adopt different definitions of HWs to systematically study the formation mechanism of urban excess warming from different climatic backgrounds, local circulation conditions, and urban morphologies.